PEMBUATAN APLIKASI WEBSITE CORPORATE PROFILE DAN PENGAJUAN WARALABA PADA UMKM ROTI TETEH - Lauro, Manatap Dolok; Natalie, Cynthia; Edison, Hans (Jurnal Serina Abdimas, 2024)
Micro, Small and Medium Enterprises (MSMEs) are one of the micro businesses that empower home industries. In an effort to increase competitiveness and expand marketing reach, MSMEs can take advantage of information technology. Several ways to increase competitiveness and marketing, one of which is to provide information about MSMEs so that more people can get this information. The development of the food and beverage home industry recently has increasingly led to brand awareness, with many of these brand owners developing their businesses by opening up opportunities for the wider community to use the MSME trade brand, namely by franchising. As a new brand, Roti Teteh faces an obstacle, namely that the name of this MSME is not well known to the public. In its young age, built in February 2022, Roti Teteh only has 1 sales location, and plans to build in other locations. Roti Teteh faces difficult competition amidst the rise of similar businesses that offer collaboration in the form of franchises. These MSMEs do not yet have the means to disseminate information about products and cooperation packages that can be accessed by the wider community. This PKM activity is concentrated on gathering needs and building a corporate profile website which is equipped with a franchise package collaboration offer feature. The results of the work have been published and well received by partners.